Hydrothermal carbonisation of raw and dewatered paunch waste: Experimental observations, process modelling and techno-economic analysis. (1st October 2021) - Hedayati Marzbali, Mojtaba; Kundu, Sazal; Patel, Savankumar; Halder, Pobitra; Paz-Ferreiro, Jorge; Madapusi, Srinivasan; Shah, Kalpit
Graphical abstract: Highlights: Hydrothermal carbonization can readily convert paunch waste to value-added products. Process modelling indicates that pre-heater and dryer are the main energy consumer. Hydrothermal carbonization technology development is challenged by reactor high cost. Treating dewatered paunch waste is more commercially viable despite lower conversion. Economic viability is highly sensitive to LHSV of reactor and economic assumptions. Abstract: In this study, dewatered and raw paunch waste, with 15 and 3 wt% total solids respectively, generated at abattoirs was hydrothermally carbonised under subcritical water conditions. Higher solids content was found to produce higher hydrochar yield (i.e. 53% for 15 wt% compared to 33.5% for 3 wt%) at similar operating conditions of 10 bar and 240 °C for 5 min. The morphological differences were noted via Scanning Electron Microscopy (SEM) in the hydrochar samples, and the surface area for processing raw paunch waste was found to be 68.1 m 2 g −1 compared to 10.8 m 2 g −1 in case of dewatered paunch waste. The light bio-oil was mostly composed of phenolic compounds while the heavy bio-oil mainly contained long chain fatty acids and their esters. Following the experimental work, a full-scale ASPEN Plus process model was developed for a typical abattoir generating 27 tonne dry paunch waste per day. Pre-heater and hydrochar dryer contributed to 73% and 57% of the total energy for processing raw and dewatered paunch waste, respectively, because of the high moisture content of the feedstock and hydrochar. After the equipment sizing and estimation of capital and operating costs, the discounted cash flow analysis was performed using the Nth-Plant financing assumptions. It was concluded that treating dewatered paunch waste is preferable as it: needed a smaller reactor i.e. lower overall initial investment, was less sensitive to bio-oil price, and improved the net present value over a period of 30 years to 2.8 MM. Besides the liquid hourly speed velocity, its commercial viability is highly sensitive to internal rate of return and existence of hydrochar dryer.